Pengendalian Persediaan Bahan Baku Alumunium Rod Wire Untuk Pembuatan Kabel Menggunakan Metode Forecasting dan Material Requirement Planning (MRP) di PT. SCC - Setiawan, Oki; Cahyana, Babay Jutika (DPPM UNIVERSITAS PELITA BANGSA, 2023)
PT. SCC is a company that manufactures types of low-voltage to high-voltage cables. The high number of requests received by the company, is often not met due to the uncertain supply of raw material for aluminum wire rods. On the other hand, the recovery in global demand for raw materials has resulted in significant shortages and price increases. This forces management to import materials from other countries, but the shipping process takes a long time which can disrupt the production process. In this study, the forecasting method used is the 3-month moving average and 5-month moving average method, the exponential smoothing method Î± = 0.80 and Î± = 0.95. The 3-month moving average method shows the smallest forecast error values, namely MAD 1,288, MSE 4,494,165 and MAPE 10.2%. To control the supply of raw materials for aluminum wire rods at PT. SCC, Lot Sizing method with Lot for Lot (LOL), Economic Order Quantity (EOQ), Period Order Quantity (POQ) and Fixed Order Quantity (FOQ) techniques. The results of the Lot for Lot technique provide optimal inventory results and the lowest total inventory costs with a total inventory cost of Rp. 126,000,000,-.